ВАРИАБЕЛЬНОСТЬ РИТМА СЕРДЦА И ДИАСТОЛИЧЕСКАЯ ДИСФУНКЦИЯ ЛЕВОГО ЖЕЛУДОЧКА У БОЛЬНЫХ ХРОНИЧЕСКИМ ПРОСТАТИТОМ - Д. Н. Зайцев (Архивъ внутренней медицины)
In order to study the relationship between the parameters of heart rate variability and diastolic left ventricular function was examined 51 patients with chronic prostatitis. All patients underwent echocardiography, were studied parameters of heart rate variability. Found that the most informative method of diagnosis of diastolic dysfunction of the left ventricle in patients with chronic prostatitis is a myocardial doppler echocardiography and violation the most indicators dynamics of blood circulation registered in the group of patients with impaired relaxation of the left ventricle. The most significant reduction in key indicators of heart rate variability occurs in patients with left ventricular diastolic dysfunction.